2005
DOI: 10.1016/j.fertnstert.2005.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in human unfertilized oocytes after intracytoplasmic sperm injection

Abstract: Objective: To investigate the presence of programmed cell death in unfertilized oocytes after intracytoplasmic sperm injection (ICSI), assuming that previous apoptotic events could be correlated with the fertilization failure. Design: Comparison of the rate of DNA fragmentation in human oocytes at different stages of maturation soon after pick-up (control) and in unfertilized oocytes after ICSI treatment. Result(s):The DNA fragmentation, by TUNEL assay, appeared in all the immature control oocytes, but only 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In this study, we used the procedures of our previous research to investigate apoptosis in human oocytes (5). A TUNEL assay and immunological tests, performed in situ with the anti-caspase-3 cleaved antibody, allowed us to highlight fragments of DNA and to confirm apoptosis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used the procedures of our previous research to investigate apoptosis in human oocytes (5). A TUNEL assay and immunological tests, performed in situ with the anti-caspase-3 cleaved antibody, allowed us to highlight fragments of DNA and to confirm apoptosis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, DNA fragmentation in oocytes associated with apoptotic evidence might be one of the reasons for poor oocyte quality and lower fertility in aged mice [11]. A study on apoptosis in human oocytes collected in ICSI cycles, showed that apoptosis occurs also in human oocytes retrieved after hormonal stimulation and it is associated to the oocyte quality [12].…”
Section: From Follicular Apoptosis New Tools In Oocyte Selection?mentioning
confidence: 99%
“…Previous data had shown DNA fragmentation in human unfertilized oocytes after ICSI, and the positivity to caspase-3 immunoassay suggested the occurrence of apoptosis. The high percentage of unfertilized oocytes bearing DNA fragmentation was correlated with fertilization failure [9]. In addition, Ruvolo et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…Among the non-invasive tools, it is possible to include specific assays on cumulus cells; these cells are in close molecular communication with the female gamete and therefore represent an interesting investigative instrument in embryology [9]. Both the expression levels of some components of intracellular survival pathways and the apoptosis rate can be assessed in cumulus cells and utilized as potential markers of oocyte competence.…”
Section: Introductionmentioning
confidence: 99%